Role of Porphyromonas gingivalis outer membrane vesicles in oral mucosal transmission of HIV - Dong, Xin-Hong; Ho, Meng-Hsuan; Liu, Bindong; Hildreth, James; Dash, Chandravanu; Goodwin, J. Shawn; Balasubramaniam, Muthukumar; Chen, Chin-Ho; Xie, Hua (Scientific reports, 2018)
The association between mucosal microbiota and HIV-1 infection has garnered great attention in the field of HIV-1 research. Previously, we reported a receptor-independent HIV-1 entry into epithelial cells mediated by a Gram-negative invasive bacterium, Porphyromonas gingivalis . Here, we present evidence showing that P. gingivalis outer membrane vesicles (OMVs) promote mucosal transmission of HIV-1. We demonstrated, using the Dynabeads technology, a specific interaction between HIV-1 and P. gingivalis OMVs which led to an OMV-dependent viral entry into oral epithelial cells. HIV-1 was detected in human oral keratinocytes (HOKs) after a 20 minute exposure to the HIV-vesicle complexes. After entry, most of the complexes appeared to dissociate, HIV-1 was reverse-transcribed, and viral DNA was integrated into the genome of HOKs. Meanwhile, some of the complexes exited the original host and re-entered neighboring HOKs and permissive cells of HIV-1. Moreover, P. gingivalis vesicles enhanced HIV-1 infection of MT4 cells at low infecting doses that are not able to establish an efficient infection alone. These findings suggest that invasive bacteria and their OMVs with ability to interact with HIV-1 may serve as a vehicle to translocate HIV through the mucosa, establish mucosal transmission of HIV-1, and enhance HIV-1 infectivity.